Deregulation of ABCG1 early in life contributes to prostate carcinogenesis in maternally malnourished offspring rats - Camargo, Ana CL. [UNESP]; Constantino, Flávia B. [UNESP]; Santos, Sergio AA. [UNESP]; Colombelli, Ketlin T. [UNESP]; Portela, Luiz MF. [UNESP]; Fioretto, Matheus N. [UNESP]; Barata, Luísa A. [UNESP]; Valente, Guilherme T. [UNESP]; Moreno, Carlos S.; Justulin, Luis A. [UNESP] (Elsevier, 2024)
Aims: The developmental Origins of Health and Disease (DOHaD) concept has provided the framework to assess how early life experiences can shape health and disease throughout the life course. Using a model of maternal exposure to a low protein diet (LPD; 6% protein) during the gestational and lactational periods, we demonstrated changes in the ventral prostate (VP) transcriptomic landscape in young rats exposed to maternal malnutrition. Male offspring Sprague Dawley rats were submitted to maternal malnutrition during gestation and lactation, and they were weighed, and distance anogenital was measured, followed were euthanized by an overdose of anesthesia at 21 postnatal days. Next, the blood and the ventral prostate (VP) were collected and processed by morphological analysis, biochemical and molecular analyses. RNA-seq analysis identified 411 differentially expressed genes (DEGs) in the VP of maternally malnourished offspring compared to the control group. The molecular pathways enriched by these DEGs are related to cellular development, differentiation, and tissue morphogenesis, all of them involved in both normal prostate development and carcinogenesis. Abcg1 was commonly deregulated in young and old maternally malnourished offspring rats, as well in rodent models of prostate cancer (PCa) and in PCa patients. Our results described ABCG1 as a potential DOHaD gene associated with perturbation of prostate developmental biology with long-lasting effects on carcinogenesis in old offspring rats. A better understanding of these mechanisms may help with the discussion of preventive strategies against early life origins of non-communicable chronic diseases.
Keywords: DOHaD; Early-life carcinogenesis; Maternal malnutrition; Prostate development